2009
DOI: 10.1542/peds.2008-2088
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Surveillance to Estimate the Burden of Rotavirus Gastroenteritis Among European Children Younger Than 5 Years of Age

Abstract: Rotavirus gastroenteritis places high demands on European health care systems, accounting for 56.2% of hospitalizations and 32.8% of emergency department visits because of community-acquired acute gastroenteritis in children aged <5 years. Most community-acquired rotavirus gastroenteritis occurs in children aged <2 years, and a high proportion occurs in infants aged <6 months. Cases were also observed among very young infants <2 months of age. Rotavirus vaccination is expected to have a major impact in reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
136
2
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(197 citation statements)
references
References 30 publications
(47 reference statements)
40
136
2
19
Order By: Relevance
“…In Europe, the new strains were initially detected in the United Kingdom (1995-1996) combined with P-type 6, which was replaced by P-type 8 in the next few years [18] A well-documented finding in this survey was the marked decrease in the current decade in the circulation of the G4 genotype. This genotype circulated widely in our environment in the 1990s but only sporadically after 1999, in line with prior reports in Spain [22] but in contrast with reports from other European regions [2,22,[24][25][26].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In Europe, the new strains were initially detected in the United Kingdom (1995-1996) combined with P-type 6, which was replaced by P-type 8 in the next few years [18] A well-documented finding in this survey was the marked decrease in the current decade in the circulation of the G4 genotype. This genotype circulated widely in our environment in the 1990s but only sporadically after 1999, in line with prior reports in Spain [22] but in contrast with reports from other European regions [2,22,[24][25][26].…”
Section: Discussionsupporting
confidence: 90%
“…The burden of rotavirus disease on the health care system was substantial during the study period, despite a remarkable decrease in the incidence of rotavirus AGE observed in the first decade of this century [12]. In line with the results of previous studies performed in developed countries in recent years, we observed predominant circulation of G1[P8] strains, the emergence of G9[P8] strains, and scarce detection of Gtype strains other than G1-G4 and G9 [2,9,[13][14][15]. In 14 of the 20 seasons after 1989, the main G-type was G1, a percentage similar to that also observed over a 20-year period (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) in Palermo, Italy [16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In developing countries, it is the leading cause of hospitalization and death among children under five, and mortality is higher in their first year of life. (1,2) In developed countries, the frequency of acute diarrhea in infants is up to two episodes/ year, whereas in developing regions it can reach ten episodes/year. Basic sanitation and drinking water almost eliminated bacterial and parasiticinfections in developed countries, but rotavirus infections are still comparable between developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%